1974
DOI: 10.1139/z74-045
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of arginine vasotocin on the isolated amniotic membrane of the guinea pig

Abstract: Amniotic membranes from fetal guinea pigs at 0.46 of term were maintained in vitro by means of salines which reproduced the electrolytes of the natural fluids, and. which maintained small osmotic and hydrostatic gradients from the fetal to the maternal solutions. Water passed slowly from the fetal to the maternal side (average rate = 3.93 mg/cm2 per minute). Synthetic arginine vasotocin (AVT) at 8–100 vasopressor mU/ml of amniotic saline slowed the fetal–maternal flow, or reversed it to give a net uptake of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1975
1975
1984
1984

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…AVT may change fetal/placental blood flow or may have a direct effect on membrane pore size. The latter hypothesis is supported by the report that AVP or AVT decrease osmolar induced water transfer from the fetal to the maternal side of the isolated guinea pig amnion in vitro when AVP or AVT are added to the fetal side of the membranes (8). Effects in this model must be due to membrane flow changes.…”
Section: Discussionmentioning
confidence: 68%
“…AVT may change fetal/placental blood flow or may have a direct effect on membrane pore size. The latter hypothesis is supported by the report that AVP or AVT decrease osmolar induced water transfer from the fetal to the maternal side of the isolated guinea pig amnion in vitro when AVP or AVT are added to the fetal side of the membranes (8). Effects in this model must be due to membrane flow changes.…”
Section: Discussionmentioning
confidence: 68%
“…Arginine vasopressin has been observed to have an effect on water flow through the guinea pig amnion in vitro. Vizsolyi and Perks [1974] and Manku, Mtabaji and Horrobin [1975] observed that the flow of water from the fetal to the maternal side of the membrane was slow or reversed in the presence of AVP. However, one case report on a woman with hydramnios [Bennebroek Gravenhorst and Wiesenhaan, 1968] indicated that AVP could cause fluid flow out of the amniotic cavity in vivo.…”
Section: Effects Of a Vp On Fetal Urinementioning
confidence: 99%
“…On the basis of these results Pavel [10] postulated that AVT may be mediating the neuroendocrine actions of the pineal gland. The action of AVT on mammalian water metab olism was investigated in vitro by Vizsolyi and Perks [38]. They found that AVT and AVP slow or reverse fetal-maternal water flux across the guinea pig amnion, a finding we have recently reported in vivo [39].…”
Section: Discussionmentioning
confidence: 98%
“…Pavel and co-workers have presented data (already cited) supporting the hypothesis that AVT secreted into CSF might mediate the hypothalamic-pituitary effects of the pineal, including the timing of onset of puberty [10,[34][35][36][37], Roles for CSF AVP and OT have not been fully defined, but there is accumulating evidence that vasopressin improves memory and learning [40]. Possible roles for AVT and AVP in water exchange across the amnion also have been alluded to [38,39], but the significance of OT in amniotic fluid remains obscure.…”
Section: Discussionmentioning
confidence: 99%